HUBUNGAN STATUS KESEHATAN GIGI DAN MUTU LAYANAN DENGAN PEMANFAATAN BALAI PENGOBATAN GIGI PUSKESMAS DI KABUPATEN TABANAN - Sagung Agung Putri Dwiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Issues with dental and oral health happens with majority of the people of Indonesia. An average of dental damages is at 5 teeth in each person, but those who are aware of their issues with regard to their teeth and mouth is only at 30% who receive treatment and medication by dental professionals. This means effective demand to have dental medication is very low. This happens in Tabanan, the effectivity of the utilization of The Dental Health Department (BPG) of Community Health Centre (Puskesmas) is very low. Some aspects of the service can influence the utilization of the health services includes the activities being done in the health such as factors of the health personnel doing the health service, facility and factor of the service users. Based on this phenomenon, this study is conducted with purpose  there is a relationship between external and internal factors with the utilization of  BPG of Puskesmas in Tabanan Regency.The method of the study was observational study with cross sectional analitic approach. The sample is taken from patients in 2 Puskesmas, that is, half of the sample of Puskesmas with number of visits   ≥ 9 persons per day  (Puskesmas Kerambitan II) and the other half from Puskesmas with number of visits 9 persons per day  (Puskesmas Selemadg Timur II) to make a total sample of 110 persons. The sample was taken from the BPG register for the period of 1 year with sampling method using systematic random  sampling.   This data to study was conducted in January until March 2012.            The result of the study indicates that there was a significant between  dental and oral health medication status , the quality of service with the utilization of BPG of Puskesmas with score of p 0,05. Out of the 2 interrelated variables, the most influencing one was the quality of service with OR= 597,551, and score of p =0,000 (p0,05).             The suggestions which can be proposed with regard to the low rate of dental health status in Tabanan Regency and the low utilization of BPG , the result of this study can become feedbacks in improving the quality of the community dental health. Program Puskesmas is to broaden its activity to School Health Care, School Dental Health Care and Village Community Dental Health Care. To improve the role of Intergrated Health Centre (posyandu) as an effective media for counseling and dental. To make effective cross sectoral meetings to promote BPG as a media for dental service with its facility. The Department of Health: To facilitate all activities being done in Puskesmas in the form of both fund and equipment. To conduct training, seminar to improve personnel competency. To regularly conduct supervision and monitoring to ke Puskesmas especially to Puskesmas with low utilization of BPG to constantly monitor the service quality on Puskesmas.